PENDAMPINGAN BACA TULIS AL-QUR’AN DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK DI TPA MARGOREJO - Kartika, Marshanda Dwi; Rahelli, Yeti; Ayunira, Lia Martha; Fitriyana, Fitriyana; Sapruddin, Sapruddin (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
The Qur’anic literacy mentoring at Al-Ikhlas TPA Margorejo aims to improve children's skills in reading and writing the Qur’an, as well as their motivation to learn. Initial observations revealed challenges such as low interest, limited teaching methods, and lack of continuous mentoring. The program began with 5 participants and grew to 10. This activity used a descriptive approach based on the ABCD principles, employing interactive methods such as fun learning and prayer practice. The results indicate positive changes in children’s learning motivation, Qur’anic reading and writing skills, and participation in congregational prayer. The program also helped facilitators develop more effective teaching methods. Despite challenges like time constraints and varying understanding among participants, the activity successfully created an enjoyable learning environment and can be implemented to enhance Qur’anic literacy sustainably. This program is expected to significantly contribute to improving religious education quality in the community. Keywords: Fun learning, Learning motivation, Quranic literacy assistance